Changing landscapes : the development of the International Tropical Timber Organization and its influence on tropical forest management - Poore, Duncan (Earthscan Publications, 2003)
This is the history of the International Tropical Timber Organization (ITTO); its aims policies and achievements through drawing on contemporary records and the author's own wide experience. The book uses examination of past successes and failures to formulate a 21st-century agenda for the most practical ways of improving the management of forests and deciding forest policies.